2017
DOI: 10.5489/cuaj.4568
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary cost-consequence analysis of blue light cystoscopy with hexaminolevulinate in non-muscle-invasive bladder cancer

Abstract: Introduction: Previous studies have suggested cost-savings using blue light cystoscopy (BLC) with hexaminolevulinate (HAL) compared to white light cystoscopy (WLC) during transurethral resection of bladder tumour (TURBT) for non-muscle-invasive bladder cancer (NMIBC), secondary to improvements in recurrence and progression rates; however, these studies have used 'best case scenario' recurrence rate probabilities, thus decreasing generalizability of the findings. The objective of this study was to perform a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…At the present time there are no long-term results on disease progression and overall survival, however it is desirable that these variables will decrease. Meanwhile the use of HAL-TURB leads to a reduction of further hospitalizations which in turn reduces hospital costs (12).…”
Section: Discussionmentioning
confidence: 99%
“…At the present time there are no long-term results on disease progression and overall survival, however it is desirable that these variables will decrease. Meanwhile the use of HAL-TURB leads to a reduction of further hospitalizations which in turn reduces hospital costs (12).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported on a range of different findings. Of the 37 studies identified from SLR searches, fifteen were cost studies, of which one evaluated total healthcare costs of bladder cancer in the US; 75 one was a US Markov model of healthcare costs by disease risk; 76 four were US database studies evaluating varying provider-level treatment intensity among Medicare beneficiaries aged ≄65 years; 12,13,77,78 three assessed diagnosis and monitoring costs; [79][80][81] three assessed different imaging technologies; [82][83][84] and two evaluated intravesical chemotherapy post-TURBT. 85,86 In addition, three budget impact models (BIMs) and eighteen CEAs were identified from SLR searches, of which twelve evaluated TURBT, mainly comparing diagnostic imaging during the procedure as well as comparing TURBT to other procedures or procedure setting.…”
Section: Economic Outcomesmentioning
confidence: 99%
“…In conjunction with WLC, BLC may improve the diagnostic accuracy of cystoscopy and facilitate a more complete tumor resection, thereby reducing the rate of tumor recurrence in NMIBC disease [10]. However, BLC is more expensive and is logistically complex compared to WLC [11]. Moreover, BLC results can be confounded by acute and chronic inflammation, such as the state of the bladder during or after a urinary tract infection(s) or in instances of traumatic penetration of the cystoscope into the bladder.…”
Section: Introductionmentioning
confidence: 99%